Identification of changes in the microflora composition of Japanese horse mackerel (Trachurus japonicus) during storage to identify specific spoilageorganisms - Daisuke Kyoui; Yuri Fukasawa; Waka Miyanaga; Yui Nakamura; Tsutomu Yamane; Kazuki Sugita; Shun Yamadera; Marie Kai; Kai Shinoda; Taketo Kawarai; Hirokazu Ogihara (Current Research in Food Science, 2022)
Japanese horse mackerel (Trachurus japonicus) is an important marine resource, and its loss and waste should be reduced. This study aimed to identify the changes in the microflora composition during storage and specific spoilage organisms (SSOs) in Japanese horse mackerel, for spoilage prevention. They were stored at either 20 °C or 4 °C aerobically, and the bacterial viable counts, concentration of total volatile basic nitrogen (TVB-N), and microflora composition for each group were analyzed. Samples stored at 20 °C for 48 h showed similar viable counts to those stored at 4 °C for 168 h; however, the TVB-N concentrations increased at 20 °C, but not at 4 °C. 16S rRNA metagenome analysis showed that Shewanella became dominant genus in the microflora regardless of the storage temperature. However, dominant amplicon sequence variants (ASVs), which are a more detailed classification level than the genus, differed depending on the storage temperatures; therefore, dominant ASVs at 20 °C were assumed to be potential SSOs. Shewanella sp. Strain NFH-SH190041, which was genetically closely related to the dominant ASVs at 20 °C, was isolated, and its spoilage ability was verified. The strain NFH-SH190041 may be considered a novel SSO of Japanese horse mackerel because its 16S rRNA sequence is clearly different from those of known species.